Edifícios de apartamentos em São Paulo: uma análise da prática do uso misto e do design de interiores entre os anos 1920 e 1940 - MONTEIRO, Silvia Bahia (2018)
This research aims to analyze the beginning of the process of residential verticalization in the city of São Paulo, since its origin in the mid-1920s until the 1940s. The choice of this period was determined by the changes in legislation regarding constructions in the city, articulated to the dissemination of the modernist culture in Brazil. Three different aspects were considered: a geographic point of view, in which we mapped the origins of the vertical development of the city in these decades; the point of view of the agents that enabled not only the verticalization but also the interior design of these spaces; and the study of mixed use buildings of the period, with their façades, floor plans and interiors. The apartment plants analyzed here were found in the archives of the Acropolis Magazine, as well as in the Iconographic Materials Section, both belonging to the Library of the Faculty of Architecture and Urbanism of the University of São Paulo; these plants were then compared to the possible uses of these spaces.